Carcinoembryonic Antigen (CEA) dan Neutrofil-to-Limfosit Ratio (NLR) sebagai Faktor Prediktif Kanker Kolorektal - Retno Martini Widhyasih; Suci Dwi Rahmadhanti; Rizana Fajrunni'mah (Poltekkes Kemenkes Jakarta III, 2019)
Colorectal cancer is a cancer that attacks the colon to the rectum. This cancer is the fourth most cancer in the world, and the second most cancer in western countries, and the third most common cause of cancer that occurs in men and women in 2012 in Indonesia. 72.4% of colorectal cancer patients have increased preoperative CEA levels, and increased NLR has been reported as a valuable predictive indicator of various types of cancer, including colorectal cancer. This study aims to analyze the correlation between CEA examination and NLR in colorectal cancer using secondary data with cross-sectional design. The sample of this study was all colorectal cancer patients in Tarakan Hospital, Central Jakarta, who examined CEA and complete hematology in 2014 - 2018. Based on the results of the study, it could be concluded that there was a correlation between CEA with NLR in colorectal cancer with a value of p = 0.000 smaller than alpha = 0.05, and the value of r = 0.78, meaning a strong correlation between CEA and NLR in colorectal cancer, so if there is an increase in CEA, it is accompanied by an increase in NLR.